Peningkatan Bisnis Golden Black Coffee oleh Tasya Farasya Melalui Konten Endorsment Di Platform Instagram Terhadap Mahasiswa KPI 5d 2024 - Nisa, Pia Khoirotun; Kultsum, Ummi; Haya, Auriel Najma; Akbar, Muhammad Fauzi; Rachman, Fadly Arief; Ramadhan, Gema Akbar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze the impact of digital marketing strategies through endorsement content on Instagram on increasing the Golden Black Coffee business, owned by Tasya Farasya. This study adopts the approach of media economic theory, social influence theory, and integrated marketing communications (IMC) to understand how promotional strategies can influence consumer behavior, especially among the younger generation. Research data was obtained through direct observation, interviews with the Golden Black Coffee marketing team, and collection of relevant documentation. KPI 5D students were selected as the target audience to understand the response to this marketing strategy. The results of the study show that Instagram as a social media platform makes a significant contribution to building brand awareness, increasing product appeal, and expanding market reach. Endorsement by Tasya Farasya has proven effective in creating emotional connections with consumers through an attractive visual approach and storytelling that is relevant to the lifestyle of the younger generation. The findings also show that the credibility and appeal of influencers play an important role in increasing trust in products and driving purchasing decisions. In addition, content diversification strategies, such as the use of Instagram Reels and Stories features, have helped strengthen the relationship between brands and consumers. This study recommends optimizing marketing strategies through platform diversification, collaboration with micro-influencers, and creating more interactive and personalized visual content. By strategically utilizing the power of social media and understanding consumer needs and preferences, Golden Black Coffee can maintain its competitive position in the market while increasing customer loyalty.